Performance analysis of CLEFIA and PRESENT lightweight block ciphers. (17th November 2019) - Jangra, Monika; Singh, Buddha
Abstract: The demand and fulfillment of various smart-needs is endangering day to day life posing security challenges. Deploying new security methods has become critical for resource-limited smart devices. NIST (National Institute of Standards and Technology) has validated CLEFIA and PRESENT among many lightweight security methods. In this paper, we have implemented lightweight CLEFIA and PRESENT encryption methods in python and evaluated them in terms of security strength, throughput and resource utilization. Our results have shown that PRESENT outperforms CLEFIA in terms of memory usage and security but CLEFIA gives better throughput than PRESENT.